Pseudomonas aeruginosa quorum sensing systems as drug discovery targets: current position and future perspectives - Soukarieh, Fadi; Williams, Paul; Stocks, Michael John; Camara, Miguel (American Chemical Society, 2018)
Antimicrobial resistance (AMR) is a serious threat to public health globally, manifested by the frequent emergence of multi-drug resistant pathogens that render current chemotherapy inadequate. Health organizations worldwide have recognized the severity of this crisis and implemented action plans to contain its adverse consequences and prolong the utility of conventional antibiotics. Hence, there is a pressing need for new classes of antibacterial agents with novel modes of action. Quorum sensing (QS), a communication system employed by bacterial populations to co-ordinate virulence gene expression, is a potential target that has been intensively investigated over the last decade. This Perspective will focus on recent advances in targeting the three main quorum sensing systems (las, rhl and pqs) of a major opportunistic human pathogen, Pseudomonas aeruginosa, and will specifically evaluate the medicinal chemistry strategies devised to develop QS inhibitors from a drug discovery perspective.